2016
DOI: 10.1007/s10552-016-0754-1
|View full text |Cite
|
Sign up to set email alerts
|

Active smoking and risk of Luminal and Basal-like breast cancer subtypes in the Carolina Breast Cancer Study

Abstract: Purpose Growing evidence suggests an association between active cigarette smoking and increased breast cancer risk. However, the weak magnitude of association and conflicting results have yielded uncertainty and it is unknown whether associations differ by breast cancer subtype. Methods Using population-based case–control data from phases I and II of the Carolina Breast Cancer Study, we examined associations between self-reported measures of smoking and risk of Luminal and Basal-like breast cancers. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…Interestingly, gene ontology analysis revealed different enrichment terms associated with smoking in HR− and HR+ tumors, with smoking-related terms in HR− tumors related to response to organic chemicals and stress, while those in HR+ tumors were associated with transcriptional regulation, suggesting that these tumor subsets may both be associated with smoking but via different pathways. Smoking-related epigenetic differences also varied somewhat by race in that the hypermethylation in HR+ breast tumors was more pronounced in black smokers, which may be consistent with epidemiologic findings from CBCS indicating that smoking was associated with the development of luminal breast cancer mainly among black women [16]. …”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Interestingly, gene ontology analysis revealed different enrichment terms associated with smoking in HR− and HR+ tumors, with smoking-related terms in HR− tumors related to response to organic chemicals and stress, while those in HR+ tumors were associated with transcriptional regulation, suggesting that these tumor subsets may both be associated with smoking but via different pathways. Smoking-related epigenetic differences also varied somewhat by race in that the hypermethylation in HR+ breast tumors was more pronounced in black smokers, which may be consistent with epidemiologic findings from CBCS indicating that smoking was associated with the development of luminal breast cancer mainly among black women [16]. …”
Section: Discussionsupporting
confidence: 68%
“…Studies in the Carolina Breast Cancer Study (CBCS) have reported the associations of smoking and breast cancer mainly among long-term smokers and recent quitters, and observed stronger associations for luminal breast cancer, particularly among African Americans [9, 16]. Additionally, we observed worse disease-specific survival among breast cancer cases who smoked (unpublished observations).…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations